2020
DOI: 10.1590/s0100-83582020380100049
|View full text |Cite
|
Sign up to set email alerts
|

Germination of Solanum nigrum L. (Black Nightshade) in Response to Different Abiotic Factors

Abstract: ABSTRACT: Solanum nigrum L. (black nightshade), an annual to short-lived perennial weed, has become a problem weed in farming systems in central China. Laboratory and greenhouse experiments were conducted to examine the influence of various abiotic factors on seed germination of black nightshade to develop effective weed control programs. Seeds germinated at a range of constant temperatures from 15 to 30 oC, but no germination occurred at temperatures below 10 oC or above 35 oC. Seeds also germinated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 34 publications
2
10
0
Order By: Relevance
“…At lower temperatures, no germination occurred in both cultivars. This is consistent with other reports for Solanum lycopersicum and Solanum nigrum, where seeds failed to germinate at low temperatures (5-10C) (Abdel et al, 2016;Dong et al 2019). This observation confirms that the African eggplant (Solanum aethiopicum L.) as related to the commonly cultivated relative (Solanum melongena L.) is a warm tropical crop and requires relatively warmer environment for germination, characterized by slow germination rates (Chen and Li, 1996).…”
Section: Effect Of Constant Temperatures On Seed Germination (G %) Of...supporting
confidence: 91%
See 3 more Smart Citations
“…At lower temperatures, no germination occurred in both cultivars. This is consistent with other reports for Solanum lycopersicum and Solanum nigrum, where seeds failed to germinate at low temperatures (5-10C) (Abdel et al, 2016;Dong et al 2019). This observation confirms that the African eggplant (Solanum aethiopicum L.) as related to the commonly cultivated relative (Solanum melongena L.) is a warm tropical crop and requires relatively warmer environment for germination, characterized by slow germination rates (Chen and Li, 1996).…”
Section: Effect Of Constant Temperatures On Seed Germination (G %) Of...supporting
confidence: 91%
“…Abdel et al, (2016) later concluded that the optimal temperature for tomato is 25C for maximum germination. Similarly, Solanum nigrum failed to germinate at higher temperatures of 35 and 40C (Dong et al, 2019).…”
Section: Effect Of Constant Temperatures On Seed Germination (G %) Of...mentioning
confidence: 98%
See 2 more Smart Citations
“…Previous studies showed that base temperature and ceiling temperature for the germination of S. nigrum populations from Sweden were 18 and 34 C, respectively (Taab and Andersson 2009). For S. nigrum populations from Hebei in China, the constant temperature range for seed germination is between 15 and 30 C (Dong et al 2020). The optimum temperature range for germination of S. nigrum for populations from India was 26 to 30 C (Suthar et al 2009).…”
Section: Introductionmentioning
confidence: 98%